AcademIK Connections: Bringing Indigenous Knowledge and Perspectives into the Classroom - Khanjan Mehta; Theodore R. Alter; Ladislaus M. Semali; Audrey Maretzki (Journal of Community Engagement and Scholarship, 2022)
Indigenous knowledge is local knowledge aggregated by communities over generations, reflecting many years of experimentation and innovation in all aspects of life. Unfortunately, positivist thinking has become the dominant epistemic culture within the academic and professional arenas and leads to the systematic marginalization of alternate ways of knowing, learning, and doing. Educating global-minded social problem-solvers necessitates bringing knowledge and perspectives of indigenous people with different epistemologies and philosophies of life into the classroom. Penn State has produced AcademIK Connections, a series of video clips that provide engaging stories about the importance of indigenous knowledge systems in developing entrepreneurial solutions to address community challenges. The video clips feature stories by individuals that, collectively, represent decades of experience in engaging with indigenous communities. These individuals come from diverse disciplines and scholarly research traditions and are known to consciously and respectfully employ indigenous knowledge in their academic activities. This paper discusses the importance of integrating indigenous knowledge into the classroom and suggests that the video series can help transform the classroom into an engaging and intriguing smorgasbord of philosophies and epistemologies.